2022
DOI: 10.1017/bec.2022.12
|View full text |Cite
|
Sign up to set email alerts
|

Lonely for Touch? A Narrative Review on the Role of Touch in Loneliness

Abstract: Loneliness is an increasingly ubiquitous topic in academic, policy, and healthcare domains. This work typically focuses on its negative physical and mental health consequences, generally employing a singular cognitive definition of loneliness. In doing so, one central aspect of our social world has been neglected in loneliness research and policy: touch. Touch is a fundamental human behaviour and a powerful form of communication which plays a role in physical and psychological wellbeing. This narrative review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…This is perspicuous when considering that touch-based bonding mechanisms are deeply rooted in human evolution 11 . If viewing loneliness as an embodied and contextualised sensory experience, the relationship with touch is clear 12 . Furthermore, the demand for more research investigating the interaction of touch and loneliness has grown 12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is perspicuous when considering that touch-based bonding mechanisms are deeply rooted in human evolution 11 . If viewing loneliness as an embodied and contextualised sensory experience, the relationship with touch is clear 12 . Furthermore, the demand for more research investigating the interaction of touch and loneliness has grown 12 .…”
Section: Introductionmentioning
confidence: 99%
“…If viewing loneliness as an embodied and contextualised sensory experience, the relationship with touch is clear 12 . Furthermore, the demand for more research investigating the interaction of touch and loneliness has grown 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 By contrast, physical connections (eg, seeing others in person, receiving and giving pats on the back and hugs) are extremely beneficial to older adults' well-being and sense of belonging. 19,20 Furthermore, while older adults in senior housing might experience social isolation, 21 researchers have shown that older adults benefit from connections with people of different generations. 21,22,23 If developed strategically, AI has immense potential for fostering social connections in old age, thereby decreasing social isolation and loneliness, especially among older adults living alone.…”
mentioning
confidence: 99%
“…For people who lived alone during COVID-19 long lockdowns, the absence of social touch was emphasised, and people spoke of a desire to hug their loved ones and to be physically close to other people again. Noone and McKenna-Plumley's (2022) narrative review argues that elements of presence, absence, and type of touch may impact upon loneliness experiences. Disentangling the relationship between loneliness and the presence/absence of wanted and unwanted touch is identified as a challenging but important avenue for future research, while practitioners are urged to consider the suitability of using touch in their work with lonely service users and clients.…”
mentioning
confidence: 99%